ANALISIS PELAKSANAAN PENYIMPANAN BERKAS REKAM MEDIS YANG TIDAK DIMUSNAHKAN DI RUMAH SAKIT ISLAM IBNU SINA PEKANBARU - Lilik Meilany; Ari Sukawan Sukawan; Nur Fadillah (Asosiasi Perguruan Tinggi Rekam Medis dan Informasi Kesehatan Indonesia- APTIRMIKI, 2017)
Archives have an important role in the process of presenting information for leaders to make decisions and satisfactory policy, therefore to be able to present complete information, quickly and correctly, there should be systems and procedures work well in the field to arsipan. Storage implementation in Islam Ibn Sina hospital pekanbaru ineffectiveness of the scanning process in the medical record file storage which is not destroyed so that when the file is needed requires a long time to look for it, it is constrained because no special power to do it. This study aims to investigate the implementation of medical record file storage which is not destroyed in Islam Ibn Sina Hospital Pekanbaru 2016. The research is descriptive qualitative research informants of 5 people, the technique used observation and interviews, data analysis using qualitative analysis, the triangulation method. The results showed that in the extermination medical record file shall be destroyed by burning exhausted all medical record file, there are 13 kinds of forms of medical records that are not destroyed and medical record file that is worth to be stored permanently in a way be scanned and stored on the hard disk in order to preserve the integrity medical record file of the damage and saves storage space outage